Moderating Effect of Team Tenure on Team Trust – Team Performance Relationship: With Relevance to Sri Lankan Tyre Manufacturing Industry - Rajapaksha, B.P.; Nishanthi, H.M. (Department of of Human Resource Management, Faculty of Commerce and Management Studies, University of Kelaniya, Sri Lanka., 2020)
Even though there are many determinants of team performance found in extend literature, team trust and team tenure's moderating effect is little investigated in the Sri Lankan context, and it has not been studied yet. Bridging the gap in the context, the current study assessed team tenure's moderating impact on team trust and team performance relationship in Sri Lankan tyre manufacturing industry. The current study was conducted as a cross-sectional study among a sample of one hundred and ninety-two executive-level employees selected from four major tyre manufacturing organizations following the stratified simple random sampling technique. Primary data were collected through a standard questionnaire distributed via Google form. The collected data were analyzed with the support the SPSS employing correlation, regression, descriptive statistics and process matrix. It is found that team tenure does not moderate the relationship between team trust and team performance, and also found that strong positive relationship between team trust and team performance. Moreover, team trust positively impacts team performance, and team tenure does not impact team trust and team performance separately. It is recommended to tyre manufacturing organizations to facilitate more open communication and information sharing to improve executive-level employees' trust within teams, which will affect their team performance.
Keywords: Team performance, Team tenure, Team trust